1997
DOI: 10.1099/0022-1317-78-10-2541
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of cytokines associated with the thrombocytopenia of equine infectious anaemia.

Abstract: Thrombocytopenia is a common finding in infection with equine infectious anaemia virus (EIAV), a lentivirus with some homology to human immunodeficiency virus (HIV). The thrombocytopenia of EIA, like that in some HIV patients, appears to have a multifactorial pathogenesis. To investigate the decreased platelet production seen in experimental EIA, the levels of three potential negative regulators of platelet production -tumour necrosis factor-α (TNF-α), transforming growth factor-β (TGF-β) and interferon-α (IFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
1
20
0
1
Order By: Relevance
“…These observations extend previous findings from visna virus (9), simian immunodeficiency virus (4), and HIV-1 (7,28) indicating that the less-differentiated cells of the bone marrow can serve as a reservoir of latently infected cells. Recent studies detected increased levels of inflammatory cytokines in the bone marrow during EIAV infection in vivo (47) and in bone marrow derived macrophages in vitro (46), which are hypothesized to suppress platelet production (5). Thus, cytokine dysregulation could result in thrombocytopenia, a clinical finding consistently associated with recrudescence of disease.…”
Section: Discussionmentioning
confidence: 99%
“…These observations extend previous findings from visna virus (9), simian immunodeficiency virus (4), and HIV-1 (7,28) indicating that the less-differentiated cells of the bone marrow can serve as a reservoir of latently infected cells. Recent studies detected increased levels of inflammatory cytokines in the bone marrow during EIAV infection in vivo (47) and in bone marrow derived macrophages in vitro (46), which are hypothesized to suppress platelet production (5). Thus, cytokine dysregulation could result in thrombocytopenia, a clinical finding consistently associated with recrudescence of disease.…”
Section: Discussionmentioning
confidence: 99%
“…TNFα (Tumor Necrosis Factor alpha) and TGFβ (Transforming Growth Factor beta) are produced by macrophages and are known to have a suppressive effect on megakaryocyte genesis. Elevation of TNFα and TGFβ has been described in days preceding the onset of thrombocytopenia [175]; Costa et al [31] described a strong correlation between TNFα production, virulence of the infecting agent and clinical outcome in vaccinated and infected animals. TNFα and TGFβ may be released by macrophages upon EIAV infection and an increase in TNFα production has been shown to coincide with the onset of fever in African Swine Fever for example [151].…”
Section: Physiopathologymentioning
confidence: 99%
“…Tornquist et al [39] demonstrated that TGF-ß protein levels determined by immunohistochemical staining were significantly higher in prethrombocytopenia bone marrow in patients with lentivirus infection. Since TGF-ß 1 is a potent inhibitor of the proliferation and differentiation of megakaryocyte progenitor cells in vivo and in vitro [14,15,[27][28][29], can TGF-ß 1 levels be significantly elevated at the prethrombocytopenic stage?…”
Section: Discussionmentioning
confidence: 99%